2002
DOI: 10.1046/j.1365-2672.2002.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of the bacteriocin-producing lactic acid cocci in Miso-paste products

Abstract: This study suggests that bacteriocin-producers act effectively as safe biopreservatives and may contribute to the biopreservation in Miso-pastes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…We recently reported that these comprised the dominant lactic acid bacteria in non-sterilized Miso products (Onda et al, 2002), which is in agreement with the findings of the present study. The halophilic and/or halo-tolerant characteristic could be a dominant factor, which would explain why these species were present throughout the entire fermentation process.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We recently reported that these comprised the dominant lactic acid bacteria in non-sterilized Miso products (Onda et al, 2002), which is in agreement with the findings of the present study. The halophilic and/or halo-tolerant characteristic could be a dominant factor, which would explain why these species were present throughout the entire fermentation process.…”
Section: Discussionsupporting
confidence: 94%
“…The strains of these groups were identified as strains of the Enterococcus faecium-'species group' (E. faecium, E. durans or E. hirae), which are known to be widespread in Miso products (Onda et al, 2002). Groups II-IV were divided according to their carbohydrate-fermentation patterns, and the selected strains were differentiated from other known enterococcal species by some of their taxonomic properties.…”
Section: Groups II Iii Iv and V: Genus Enterococcus (607 Strains; 8mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of bacteriocins, antimicrobial peptides, are produced by many lactic acid bacteria (LAB) (Onda et al, 2002, Soriano et al, 2004, Sparo et al, 2006. Since bacteriocins are isolated from foods, such as meat and dairy products, which normally contain LAB, they have unknowingly been consumed for centuries by humans (Goktepe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The spoilaging phenomena seriously deteriorate the quality of sake. To prevent hiochi from emerging in the sake brewing industry, pasteurization (hiire) at around 65℃ for a short duration of 2-3 min or microfiltration for removing hiochibacteria has been carried out in the sake brewing process.However, the spoilage of sake caused by hiochi-bacteria is not completely repressed at present.A large number of bacteriocins, antimicrobial peptides, are produced by many lactic acid bacteria (LAB) (Onda et al, 2002, Soriano et al, 2004, Sparo et al, 2006. Since bacteriocins are isolated from foods, such as meat and dairy products, which normally contain LAB, they have unknowingly been consumed for centuries by humans (Goktepe, 2006).…”
mentioning
confidence: 99%